2019
DOI: 10.3390/app9235134
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Flow Mechanisms and the Performance Change of a Highly Loaded Axial Compressor Stage with/without Stator Hub Clearance

Abstract: Three-dimensional corner separation is common in axial compressors, which can lead to large flow loss and blockage especially when it evolves into the corner stall (open separation). In this paper, the evolution of the three-dimensional flow structures inside a cantilevered stator of a 1.5 stage low-speed highly loaded axial compressor as the stator hub clearance varies, and its effect on the whole compressor performance are investigated experimentally. Firstly, when the stator hub is sealed, the hub corner st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Compared to uniform gaps and contraction gaps, expansion gaps had a greater weakening effect on leakage flow and were more effective in suppressing leakage vortices. Liu et al 20 explored the flow mechanism of different gaps in cantilever stators. They analyzed the influence of four different gaps: 0%, 0.25%, 0.5%, and 1.0% of the blade height on the aerodynamic performance of the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to uniform gaps and contraction gaps, expansion gaps had a greater weakening effect on leakage flow and were more effective in suppressing leakage vortices. Liu et al 20 explored the flow mechanism of different gaps in cantilever stators. They analyzed the influence of four different gaps: 0%, 0.25%, 0.5%, and 1.0% of the blade height on the aerodynamic performance of the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…The radial clearance of the stator has been optimized to the appropriate size to ensure that only traditional hub leakage flow exists in the region. Meanwhile, no corner separation occurs from choke to stall according to the study by Liu et al [30]. The entire stage also contains an inlet guide vane (IGV), which is omitted in this study to reduce calculations.…”
Section: Geometric Parametersmentioning
confidence: 99%
“…Analogous work on blade tip clearance is being carried out for stators. It has shown by Liu et al [24] that, although stators are not rotating components, the phenomena occurring in the area of the blade tip of the stators are the same as those for rotor blades. Experimental testing has shown that clearances smaller than approximately 0.5% of the blade chord is also not optimal for compressor stability.…”
Section: Compressor Researchmentioning
confidence: 99%